Costs of energy efficiency mandates can reverse the sign of rebound - Don Fullerton; Chi L. Ta (Center for Economic Studies and ifo Institute (CESifo), 2019)
Improvements in energy efficiency can reduce costs of consuming services from cars and appliances and result in positive rebound that offsets part of the direct energy reduction. Our analytical general equilibrium model decomposes rebound into direct and indirect effects. A costless technology shock has positive rebound as in prior literature, but a pre-existing energy efficiency standard can negate direct energy savings from that shock. For increased stringency of energy efficiency standards, however, we show how income effects reduce energy use for both services and other goods. We show exactly when those increased costs imply negative total rebound.
Keywords: Q48; 330